In Vitro Evaluation of Biocompatibility and Immunocompatibility of 2,3 Dialdehyde Cellulose Hydrogel Membranes for Wound Healing - Lacin, NelisaTurkoglu; Kaplan, Engin; Demirbilek, Murat; Mazmanci, Mehmet Ali; Mazmanci, Birgul; Cavas, Tolga (AMER SCIENTIFIC PUBLISHERS, 2017)
Bacterial cellulose is a hydrogel with high water holding capacity due to its natural three-dimensional nanofiber structure which allows it to use in wound dressings. In the present study, bacterial cellulose modified to 2,3 dialdehyde bacterial cellulose (DABC) to obtain biodegradable membranes and then loaded with ampicillin (AMP). Keratinocyte and fibroblast cells were cultured on the membranes to evaluate the membrane's biocompatibility. Results revealed that DABC membranes stimulated keratinocyte and fibroblast cell proliferation as the result of increased surface area compared to the non-degradable. In vitro, immunocompatibility tests of membranes showed that wound dressing material has no immunostimulatory effect. In vitro, immunocompatibility of hydrogel was evaluated by determination of interleukin 10 and tumor necrosis factor levels in medium. No significant increase in the levels of IL-10 and TNF-alpha observed. AMP encapsulation rate and AMP release profiles were determined by LC-tandem mass spectrometer. The AMP amount was determined 9.18 mg per cm(2). In vitro antibacterial tests of AMP containing DABC membranes have demonstrated their ability to inhibit Escherichia coli and Staphylococcus aureus growth. This novel AMP loaded DABC membrane seems to be highly suitable for skin wound therapy due to its antimicrobial effectiveness, immunocompatibility, biodegradability, and biocompatibility.
Keywords: Immunocompatibility; Dialdehyde Bacterial Cellulose; Ampicillin; Biodegradable Wound Dressing; BACTERIAL CELLULOSE; PERIODATE-OXIDATION; GROWTH-FACTORS; DELIVERY; NANOPARTICLES; CYTOKINES; Cell Biology